Publisher Correction: Post-transcriptional gene regulation by mRNA modifications. Issue 12 (December 2018) - Zhao, Boxuan; Roundtree, Ian; He, Chuan
In Figure 5, translation initiation is promoted not by the indicated protein, but by YTHDF1 (see below).